1998
DOI: 10.1021/bi972803d
|View full text |Cite
|
Sign up to set email alerts
|

Dual Regulation of the Skeletal Muscle Ryanodine Receptor by Triadin and Calsequestrin

Abstract: Triadin, a calsequestrin-anchoring transmembrane protein of the sarcoplasmic reticulum (SR), was successfully purified from the heavy fraction of SR (HSR) of rabbit skeletal muscle with an anti-triadin immunoaffinity column. Since depletion of triadin from solubilized HSR with the column increased the [3H]ryanodine binding activity, we tested a possibility of triadin for a negative regulator of the ryanodine receptor/Ca2+ release channel (RyR). Purified triadin not only inhibited [3H]ryanodine binding to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
80
2
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 35 publications
3
80
2
2
Order By: Relevance
“…Since its initial discovery in 1990 , triadin has been shown to be enriched and embedded in the SR membrane of the triad (Knudson et al, 1993a), to interact directly with both CSQ and RyR1 (Guo and Campbell, 1995), to inhibit RyR channels when applied to the cytoplasmic side (Ohkura et al, 1998), to activate channels when applied to the luminal side (Gyorke et al, 2004), and to contribute to the luminal Ca 2+ transduction machinery that regulates Ca 2+ release channel activity in skeletal muscle (Beard et al, 2004). Lee et al (2004) identifi ed three negatively charged amino acids (D4878, D4907, and E4908) in an RyR1 luminal loop that were each required for the isolated loop to bind a specifi c positively charged triadin KEKE motif (residues Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its initial discovery in 1990 , triadin has been shown to be enriched and embedded in the SR membrane of the triad (Knudson et al, 1993a), to interact directly with both CSQ and RyR1 (Guo and Campbell, 1995), to inhibit RyR channels when applied to the cytoplasmic side (Ohkura et al, 1998), to activate channels when applied to the luminal side (Gyorke et al, 2004), and to contribute to the luminal Ca 2+ transduction machinery that regulates Ca 2+ release channel activity in skeletal muscle (Beard et al, 2004). Lee et al (2004) identifi ed three negatively charged amino acids (D4878, D4907, and E4908) in an RyR1 luminal loop that were each required for the isolated loop to bind a specifi c positively charged triadin KEKE motif (residues Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate a strong functional consequence of triadin binding to WT RyR1 and the lack of any functional change when triadin is added to triadin binding-defi cient ∆M 1,2,3 channels. Previous studies have shown an inhibitory interaction between the cytoplasmic domain of triadin and RyR1 (Ohkura et al, 1998;Groh et al, 1999).…”
Section: Ryr1 Mutations That Disrupt Triadin Binding Do Not Directly mentioning
confidence: 90%
“…In skeletal muscle, triadin has been shown to inhibit the calcium channel activity of purified RyR (18,19). These experiments were the first to identify a function of triadin in skeletal muscle, and they led to the conclusion that triadin could regulate RyR function via inhibition of the channel.…”
mentioning
confidence: 98%
“…Beyond simply anchoring calsequestrin to the ryanodine receptor, triadin may affect the channel activity of the ryanodine receptor directly. For example, application of skeletal muscle triadin to the purified ryanodine receptor incorporated in planar lipid bilayers inhibits the channel activity of the protein (18,19). As part of a program to better understand the function of junctional SR proteins in myocardium, we initiated a strategy in which key junctional SR proteins are overexpressed in transgenic mouse hearts.…”
mentioning
confidence: 99%